Winningham and Preusser's critical thinking in medical-surgical settings : - Preusser, Barbara A. (New Jersey, 2005)
Drawing upon actual clinical experiences and case studies, the 3rd edition of this popular reference stimulates critical thinking while bridging the gap between knowledge and clinical practice. Each of the 14 chapters are organized by specific body system disorders and feature cases integrating pharmacology, nutrition, and diagnostic/laboratory tests. The introduction of 15 brand-new cases provides real-life examples to test reader knowledge on a variety of clinical settings including acute, community, home, and long-term care. In addition, there are three new chapters on women's health disorders, psychiatric disorders, and alternative therapies.